Indicadores de desempenho estratégico para uma incubadora de empresas de base tecnológica: uma proposta - Luiz Amaro Lanari (2000)
A proposal of a minimum set of strategic performance indicators was structured and presented in this dissertation based on a field research of the Biominas Foundation business incubator and a bibliographic revision focused on the value of information in managerial and strategic information systems and in the balanced scorecard methodology of strategic management. This paper has five chapters. The first one analyses the role of a business incubator in the acceleration of the technological innovation process. In the second one the value of information is discussed either alone or in management and strategic information systems. In chapter three the relationship between technological development and information is discussed. In the fourth chapter, the concept of business incubation is analysed and the Fundação Biominas business incubator is examined in search of sets of strategical performance indicators used by the business incubator management or by various institutional partners. In the fifth chapter, as a synthesis of theoretical and field findings, a proposal of a minimum set of strategic performance indicators for a business incubator is structured and presented